News Networks in Early Modern Europe - Raymond, Joad; Moxham, Noah (Library of the Written Word - The Handpress World, 2016)
In News Networks 35 scholars from 10 countries give a new account of the history of European news, emphasising its transnational character and the international transmission of forms and modes of news as well as information. Readership: All interested in the histories of news, of the book, and of political culture in early modern Europe.